Predictive Stressors of Schizophrenic Patients’ Family - Mashudi, Sugeng; Yusuf, Ah.; Triyoga, Rika Subarniati; Nasriati, Ririn; Armyati, Eky Okviana (International Journal of Psychosocial Rehabilitation, 2020)
Family stress is a type of response from a family living with schizophrenic patients, perceived as challenges and threats. Schizophrenia impacts not only the sufferers but also their family and community around them. Patient factors and family factors may become stress predictor of schizophrenic patients’ families. Around 90% of schizophrenic patients living with their families will affect the family’s socio- economic condition. Family stress is perceived as a threat because it may decline the quality of caring, while family stress as a challenge is perceived as whether it guarantees the stability of schizophrenic patients’ condition. This study aimed to predict a stress model of schizophrenic patients’ families in Ponorogo.The population was family with schizophrenic patients who undergo outpatient care in primary healthcare centers for mental health in Ponorogo. This study was cross-sectional, using a simple random sampling to select 30 respondents as the sample. The independent variable included stigma, family role, and adherence to taking drugs. Data were collected through questionnaires that were modified and tested for validity and reliability. Data analysis was done by using SMART PLS to identify a stress model of schizophrenic patients’ families in Ponorogo.Results show that family stress model involves stigma and adherence to drugs, but the family role does not show a significant value. The coefficient value of stigma on family stress is at 0.278, meaning that one higher point of stigma influences family stress at 0.278. Meanwhile, the coefficient value of adherence to drugs is 0.573, indicating that one higher point may incline family stress at 0.573. Further research may be done to identify a stress model of schizophrenic patients’ families by scrutinizing the environment factor and health worker factor. Thus, it may lead to a more complex stress model.